2010
DOI: 10.1021/cm1028782
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Doped RuO2 electrocatalyts for Selective Oxygen Evolution: Relationship between Local Structure and Electrocatalytic Behavior in Chloride Containing Media

Abstract: Nanocrystalline electrocatalytically active materials of chemical composition Ru 1-x Zn x O 2 (0< x < 0.3) were synthesized by freeze-drying technique. The diffraction patterns of the prepared samples corresponded to single-phase rutile type oxides. Local structure of the Ru 1-x Zn x O 2 based on refinement of Ru K and Zn K edge EXAFS functions shows clustering of the Zn ions in the blocks with ilmenite structure intergrowing with Ru-rich rutile blocks. Ru 1-x Zn x O 2 oxides are selective catalysts for anodic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 17 publications
4
86
2
Order By: Relevance
“…In this regard, the mechanisms by which Zn and Ti increase activity in the ternary RuO 2 based electrocatalysts seem to be different. In the co‐electrodeposited RuZn electrode, the presence of Zn atoms in the subsurface region causes distortion of the local surface structure of RuO 2 , which lowers the activation energy for electrocatalytic water oxidation, as suggested by DFT studies . Tafel‐slope analysis and the higher exchange‐current density of the Zn‐doped RuO 2 catalyst in comparison to the RuO 2 catalyst also support this hypothesis.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…In this regard, the mechanisms by which Zn and Ti increase activity in the ternary RuO 2 based electrocatalysts seem to be different. In the co‐electrodeposited RuZn electrode, the presence of Zn atoms in the subsurface region causes distortion of the local surface structure of RuO 2 , which lowers the activation energy for electrocatalytic water oxidation, as suggested by DFT studies . Tafel‐slope analysis and the higher exchange‐current density of the Zn‐doped RuO 2 catalyst in comparison to the RuO 2 catalyst also support this hypothesis.…”
Section: Resultsmentioning
confidence: 75%
“…From this we infer that most of the Zn is present in the subsurface region. Previous DFT studies indicated that subsurface Zn is responsible for lowering the activation energy of the OER . Furthermore, Ru 0.258 Ti 0.736 Zn 0.006 O x and Ru 0.33 Ti 0.67 O x have nearly equal amounts of Ru and Ti atoms on the surface.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[57] Indeed, CER is typically favored over OER at acidic conditions. [62,63] More recent work used similar doped manganese oxides [52,64] and other doped oxides [59,61,65] to selectively produce oxygen even under acidic brine conditions with reasonable selectivity. [57,[59][60][61] Oxygen-selective catalysts in acidic chlorinated conditions are relatively underexplored, yet afew promising early studies have reported selectivity for oxygen production from seawater by using doped manganese oxides.…”
Section: Summary Of Membrane-based Pretreatment Processes For Brine Vmentioning
confidence: 99%
“…Reprinted from ref [65]. For10% Zn, oxygen is selectively formed over chlorine gas at most potentials.…”
mentioning
confidence: 99%